[Earth science] - Stoebarger, Bill; Hawkhill Associates Inc. (Wisconsin : Hawkhill Associates Inc., 2002)
Tells how climate and weather have changed through the ages and how those changes were detected. Gives an overview of the modern fundamentals of weather and climate generation. Also an introduction to geology and geography, as well as a discussion of the history and development of these sciences
Title from disc label
Vol. 1. : Program 1. Climate, weather & people. Part 1. Climate and weather through the ages. part 2. Climate and weather today. - program 2. The changing earth. part 1. Pioneers in the earth science. part 2. The changing earth today
Editors, Bill Stonebarger, Michael Stonebarger ; music, Michael Stonebarger ; graphics, Lin Haley, Michael Stonebarger, Doug Mormington ; videographers, Jane Denny, Michael Stonebarger, Bill Stonebarger
Keywords: Geology, Structural; Climatic changes; Climatology; Weather; Meteorology